METODE BERTEOLOGI PAULUS MENURUT 1 KORINTUS 9:1-23 DALAM KONTEKS MASA KINI - E. Chrisna Wijaya; Asih Rachmani Endang Sumiwi; Joseph Christ Santo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The method of theology used by a person in providing theological understanding has a uniqueness or distinctiveness that can be judged and even imitated by other theological learners. What the Apostle Paul had and did became an example for believers in his time and today, amid the demands of a society that is increasingly moderate and increasingly sensitive to the gospel message, not only in terms of setting an example of life but also setting an example in terms of theology. The author uses qualitative research methods in discussing and studying specifically 1 Corinthians 9:1-23 in order to examine and discover Paul's theological method. In the study, the author found three theological methods used by the Apostle Paul in this context: the rhetoric method, the apologetics method, and the contextual method. In today's context, the rhetorical method enables effective speech by choosing words, terms, expressions, and sentences that can attract the attention and sympathy of the listener. The apologetic method pays attention to the substance of the true truth of the Christian faith without getting bogged down in the demands of the perspective of the average society. The contextual method pays attention to the condition of society, culture, and all its characteristics, with the aim that the gospel is preached and people in that context can accept and know Christ.